If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = 7 + 6x Solving -13 = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -13 + -6x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 -13 + -6x = 7 + 0 -13 + -6x = 7 Add '13' to each side of the equation. -13 + 13 + -6x = 7 + 13 Combine like terms: -13 + 13 = 0 0 + -6x = 7 + 13 -6x = 7 + 13 Combine like terms: 7 + 13 = 20 -6x = 20 Divide each side by '-6'. x = -3.333333333 Simplifying x = -3.333333333
| 138.88=2.85h+73.33 | | n^2+n-92=0 | | 12x-5y+30=0 | | 5a-4=2a+56 | | -5(-4u+4)-6u=2(u-7)-4 | | 23x=374737 | | 6x^2+12x=963 | | c*2.1+c*4+4=12 | | 4(3n-7)=-3(-2n+8) | | 9+s=6 | | 6x-30=4x-6 | | 24u^4v^7-18uv^2x^6=0 | | 3x-8x=-27-13 | | 8x-4=10x+14 | | 0=2x^2-3x+4 | | T^4+9t^4= | | x^2+10x+14=5 | | (4y-6)(2y+4)=0 | | -3(w+5)=3w-7+2(2w+5) | | 4(3-2)=16q | | c+c*7+2=12 | | 4(3n-7)+3=-3(-2n+8) | | 5b+9=7+2b | | -0.7w=5.6 | | 5x+27=2x+12 | | -11+9-2x-11-1=-13 | | 8t=400 | | (a+8)(a+2)=0 | | (x^2-x-1)(x^2-x-1)=5+x^3 | | (x^2-x-1)=5+x^3 | | (x^2-x-1)=5+x | | 7+4(3v-4)=-3(3v-3)+7v |